1994
DOI: 10.1038/clpt.1994.186
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of midazolam in neonates

Abstract: Objective: To describe the pharmacokinetics of midazolam, a water-soluble benzodiazepine with a short half-life, in critically ill neonates. Hypothesis: Midazolam clearance is reduced in neonates compared with clearance in children, and the doses currently in use, which are derived from pediatric studies, are excessive. Patients and Methods: This population study was conducted in 187 neonates requiring intravenous sedation for artificial ventilation. The 531 midazolam concentration measurements obtained were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
93
0
5

Year Published

1996
1996
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(113 citation statements)
references
References 0 publications
15
93
0
5
Order By: Relevance
“…Invariably, the patients studied are critically ill, which is likely to contribute to the wide variability in study results. The largest study is a population based study (Burtin et al 1994) which involved determining serum midazolam concentrations in 187 neonates (gestational age 26-42 weeks, postnatal age 0-10 days) on artificial ventilation. This population study found clearance to be directly proportional to birth weight and gestational age, but not postnatal age (between 0-10 days).…”
Section: Midazolammentioning
confidence: 99%
“…Invariably, the patients studied are critically ill, which is likely to contribute to the wide variability in study results. The largest study is a population based study (Burtin et al 1994) which involved determining serum midazolam concentrations in 187 neonates (gestational age 26-42 weeks, postnatal age 0-10 days) on artificial ventilation. This population study found clearance to be directly proportional to birth weight and gestational age, but not postnatal age (between 0-10 days).…”
Section: Midazolammentioning
confidence: 99%
“…However, several in vitro studies have shown that P450s are not uniformly expressed from the prenatal period to adulthood and that ontogenesis is a highly variable process. Many of these differences are of direct significance for pediatric clinical practice, because the rate of P450-dependent metabolic clearance of drugs such as midazolam (Burtin et al, 1994) and theophylline (Hendeles and Weinberger, 1983) cannot be simply extrapolated from body weight adjustments or from data on P450 expression and regulation in adults.…”
mentioning
confidence: 99%
“…The lack of data on the pharmacokinetics of many drugs in neonates and children is related to blood sampling limitations for this population. One way around this problem is to collect a few samples from many individuals and analyze the data by means of a population-based approach (7,10,13,14,29,34,51,54). The administration of aminoglycosides once daily has been shown to be as well tolerated as or better tolerated than the conventional schedules (twice daily or thrice daily) in adults and children.…”
mentioning
confidence: 99%